In luck we trust: Capturing the diversity bonus through random selection - Chengwei Liu (Journal of Organization Design, 2021)
Complex tasks often cannot be addressed with expertise, but instead by assembling a diverse cognitive repertoire in teams. In such cases, engaging diversity may enhance performance. Yet various behavioral and social limits often deter organizations from recognizing or integrating valuable diversity. I argue that random selection is an undervalued tool for capturing the diversity bonus because it helps address: (1) the paradox of merit, by avoiding fruitless deliberation; (2) biased reasoning, by deciding on the basis of no reason; and (3) learning traps, by discovering self-confirming false beliefs. More generally, incorporating random selection in organizational design can generate a less-is-more effect: deciding by blind luck means exercising less control over outcomes but achieving more by saving time and resources, as well as detecting and sanitizing biased reasons.
Keywords: 650; Random selection; Diversity bonus; Luck; Decision biases; Paradox of merit; Learning traps